Role of Serum Vitamin D Level in the Progression of Dengue Viral Illness: A Potential Immunomodulator?: A Literature Review - Limbu, Binod; Chaudhary, Birochan Kumar; Jha, Suraj Kumar (Journal of Multidisciplinary Research Advancements, 2024)
This is a literature review on the role of serum vitamin D levels in dengue viral illness as a potential immunomodulator. The dengue virus is an RNA virus that causes many symptoms, from asymptomatic phases to severe forms like dengue hemorrhagic fever and dengue shock syndrome. The review methodology was based on evidence-based rapid review, and the review’s objectives are to scrutinize all the available articles on dengue virus and vitamin D from standard databases and literature searches. It was found that there are no specific antivirals for the definitive management of the dengue virus, and vitamin D, with its potential antiviral and immunomodulatory effects, can play a significant role against the dengue viral illness. It was also found that there are limited reviews on the association between dengue virus and vitamin D. The review concludes that there is a possible association between supplementing with vitamin D and lowering the risk of progression to severe dengue viral illness and that regular testing of serum vitamin D levels is highly encouraged during the illness as vitamin D levels get depleted with the progression of the illness.